New record of Abelisauroid Theropods from the Bauru group (upper cretaceous), São Paulo State, Brazil - Méndez, Ariel Hernán (2014)
Isolated bones of abelisauroid theropods from the Bauru Group (Late Cretaceous, Brazil), are described. They correspond to three individuals represented by fused ischia and part of the ilium, a partial axis, and a right fi bula, respectively. The fossils come from different sites in the municipalities of Ibirá (axis and fi bula) and Monte Alto (ilium and ischia), São Paulo State, from Maastrichtian beds of the São José do Rio Preto and the Marília formations (Bauru Group), respectively. The specimens provide new information on abelisauroids which are still poorly known in the Brazilian fossil record, and on the distribution of this diverse group of theropod dinosaurs in South America. These discoveries indicate that abelisauroids were the most common large predatory dinosaurs in the outcrops where they come from.